Implicit and Explicit Teaching of Grammar: An Empirical Study - Mendoza López Edgar (Profile: Issues in Teachers' Professional Development)
This is a report on the experimental phase of a two-stage study on the effects of implicit-explicit grammar instruction regarding EFL students’ performance. The purpose of this phase was to investigate whether the methodologies of
implicit and explicit EFL instruction account for the improvement of university students’ performance on a test over two grammar topics. Three groups were selected. Students in the implicit language classes had no explicit instruction on these topics which were taught through meaningful and contextualised listening, speaking, reading and writing activities. Students in the explicit language classes were taught the regular course plus additional exercises and drills in order to practise the grammatical features, and a control group was taught the regular course. The results indicate that students in the explicit
instruction group achieved significantly higher scores than both the students in the implicit instruction group and the students in the control group on the performance tests.

Key words: Grammar-Input, Implicit-Grammar, Explicit-Grammar, Grammar- Teaching, Quantitative-Research

Éste es un informe de la fase experimental de un estudio en dos etapas sobre los efectos de la enseñanza implícita y explícita de la gramática en el desempeño de los estudiantes. El propósito de esta etapa era investigar si las metodologías implícita y explícita se relacionaban con el mejoramiento de estudiantes universitarios en una prueba sobre dos temas gramaticales. Se seleccionaron tres grupos: los estudiantes en el grupo de instrucción implícita no tuvieron ninguna instrucción explícita en los dos tópicos que se enseñaron a través de actividades significativas y contextualizadas en escucha, habla, lectura y escritura.
El grupo de instrucción explícita tomó el curso regular ofrecido por la institución más actividades y ejercicios extras con el propósito de practicar los temas gramaticales enseñados; y el grupo de control tomó únicamente el curso regular. Los resultados indican que los estudiantes en el grupo de enseñanza explícita lograron resultados significativamente más altos que los estudiantes en el grupo
de enseñanza implícita y que los estudiantes del grupo de control.

Palabras claves: Input-Gramatical, Gramática-Implícita, Gramática- Explícita, Enseñanza-Gramática, Investigación-Cuantitativa